Peripheral and central changes induced by neural mobilization in animal models of neuropathic pain: a systematic review - Salniccia, Federico; de Vidania, Silvia; Martinez-Caro, Leticia (Frontiers in Neurology, 2024)
Introduction Neural mobilization (NM) is a physiotherapy technique involving the passive mobilization of limb nerve structures with the aim to attempt to restore normal movement and structural properties. In recent years, human studies have shown pain relief in various neuropathic diseases and other pathologies as a result of this technique. Improvement in the range of motion (ROM), muscle strength and endurance, limb function, and postural control were considered beneficial effects of NM. To determine which systems generate these effects, it is necessary to conduct studies using animal models. The objective of this study was to gather information on the physiological effects of NM on the peripheral and central nervous systems (PNS and CNS) in animal models. Methods The search was performed in Medline, Pubmed and Web of Science and included 8 studies according to the inclusion criteria. Results The physiological effects found in the nervous system included the analgesic, particularly the endogenous opioid pathway, the inflammatory, by modulation of cytokines, and the immune system. Conclusion On the basis of these results, we can conclude that NM physiologically modifies the peripheral and central nervous systems in animal models.